Study Hypothesis: Age, Gender, Presence of Diabetes Mellitus or Hypertension, and Anti-Hypertensive Drugs Are Independent Risk Factors for COVID-19 Mortality - Faruk Karandere; Hakan Kocoglu; Ramazan Korkusuz; Betul Erismis; Mehmet Hursitoglu; Kadriye Yasar Kart (Acta Clinica Croatica, 2023)
We aimed to investigate the effects of comorbid diseases and antihypertensive drugs on the clinical outcome of hospitalized patients with COVID-19 infection. A total of 1045 patients whose data could be gathered and confirmed from both hospital files and Turkish National Health Network records were retrospectively screened, and 264 of 1045 patients were excluded because of having more than one comorbid disease. The study population consisted of a total of 781 patients, of which 482 had no comorbid disease, while the remaining 299 patients had only one comorbid disease. The mortality risk was 7.532 times higher in those over 65 years of age compared to cases younger than 30 years (OR: 7.532; 95% CI: 1.733-32.730); the risk of mortality in men was 2.131 times higher than in women (OR: 2.131; 95% CI: 1.230-3.693); and presence of diabetes mellitus (DM) increased mortality risk 2.784 times (OR: 2.784; 95% CI: 1.288-6.019). While hypertension was not found to be an independent risk factor for COVID-19 mortality, age, gender, and presence of DM were independent risk factors for COVID-19 mortality. There was no association between antihypertensive drugs and mortality. Accordingly, age (>65 years), gender (male), and presence of DM were independent risk factors for COVID-19 mortality, whereas hypertension and use of angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and their combinations with other antihypertensive drugs were not risk factors for COVID-19 mortality.